Present status of pond fishery in Dhamairhat Upazila, Naogaon - Hossain, M Abul; Khan, M Ataur Rahman; Mannan, M Abdul (University Journal of Zoology, Rajshahi University, 2007)
Key words: pond fishery; Dhamairhat Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 79-80